Efficacy of Oral Voriconazole in the Treatment of Dermatophyte Infections (Tinea Corporis and Cruris) - Shahzad, Muhammad Khurram; Hassan, Tahir; Tahir, Raheel; Jawaid, Kalsoom; Khan, Muhammad Farooq; Naveed, Muhammad Abdullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the efficacy of oral voriconazole in the treatment of dermatophyte infections (tinea corporis and cruris) Methodology: A total of 200 patients of both sex with age group 18-60 year having dermatophyte infection of body and groin were enrolled in this study. Each patient was given oral voriconazole 200 mg twice a day (tablet vorif 200 mg) for two weeks. Follow up was done at end of 2nd, 4th and 12 weeks. Efficacy was assessed clinically in the form of complete healing of lesion leaving behind post inflammatory pigmentation or normal skin. Study duration was 3 months. Patients were assessed for any possible side effects at each appointment. All of the patients were truly monitored and checked for their compliance to drug. The data was recorded on preformed Proforma for each patient. Results: Out of 200 cases, 133 were new, 42 were relapsing and 25 were resistant cases. Total efficacy was noted in 164 patients (82%) of all study cases. Male and female showed efficacy in 81% and 82% of cases respectively (Table 1). Patients belonging to age group 18-40 year showed 86 % efficacy and patients belonging to age group 41-60 year showed 76% efficacy (Table 2). From all new, relapsing and resistant study cases, 90 %, 71% and 58% showed efficacy to treatment respectively (Table 3). Conclusion: In our population oral voriconazole is efficacious in the treatment of tinea corporis and cruris.